2022
DOI: 10.1177/07340168221098371
|View full text |Cite
|
Sign up to set email alerts
|

PTSD as a Predictor of Differential Development of Dual Systems Model Constructs: A Group-Based Trajectory Modeling Approach

Abstract: The dual systems model is a prominent framework for understanding how differential cognitive development of impulse control and sensation-seeking predicts peak involvement in risky behaviors during adolescence. This study examines heterogeneity in the development of dual systems constructs and examines post-traumatic stress disorder as a driver of differential development. This study utilized data from all 11 waves of the Pathways to Desistance study. Group-based trajectory modeling was used to identify hetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…10,26,27,28 Despite this, understanding departures from typical developmental patterns of these constructs remains understudied, though some research has examined this topic and indicated the relevance of traumatic stress for driving heterogeneity. 29 A recent provides an outline of potential mechanisms underlying the relationship between traumatic stress and sensationseeking; 30 indicating that such exposures may lead to drives towards reliving of traumatic events, impaired risk recognition and insecure attachment and relational insecurity, among others. As such, individuals who experience traumatic stress like exposure to violence may develop post-traumatic risk-seeking, and it is established that this may be linked to justice-system involvement due to involvement in illegal behaviour, like substance use.…”
Section: The Dual Systems Model Exposure To Violence and Substance Usementioning
confidence: 99%
“…10,26,27,28 Despite this, understanding departures from typical developmental patterns of these constructs remains understudied, though some research has examined this topic and indicated the relevance of traumatic stress for driving heterogeneity. 29 A recent provides an outline of potential mechanisms underlying the relationship between traumatic stress and sensationseeking; 30 indicating that such exposures may lead to drives towards reliving of traumatic events, impaired risk recognition and insecure attachment and relational insecurity, among others. As such, individuals who experience traumatic stress like exposure to violence may develop post-traumatic risk-seeking, and it is established that this may be linked to justice-system involvement due to involvement in illegal behaviour, like substance use.…”
Section: The Dual Systems Model Exposure To Violence and Substance Usementioning
confidence: 99%